Vitamin E-infused highly cross-linked polyethylene did not reduce the number of in vivo wear particles in total knee arthroplasty. (3rd November 2020) - Orita, Kumi; Minoda, Yukihide; Sugama, Ryo; Ohta, Yoichi; Ueyama, Hideki; Takemura, Susumu; Nakamura, Hiroaki
Abstract : Aims: Vitamin E-infused highly cross-linked polyethylene (E1) has recently been introduced in total knee arthroplasty (TKA). An in vitro wear simulator study showed that E1 reduced polyethylene wear. However there is no published information regarding in vivo wear. Previous reports suggest that newly introduced materials which reduce in vitro polyethylene wear do not necessarily reduce in vivo polyethylene wear. To assist in the evaluation of the newly introduced material before widespread use, we established an in vivo polyethylene wear particle analysis for TKA. The aim of this study was to compare in vivo polyethylene wear particle generation between E1 and conventional polyethylene (ArCom) in TKA. Methods: A total of 34 knees undergoing TKA (17 each with ArCom or E1) were investigated. Except for the polyethylene insert material, the prostheses used for both groups were identical. Synovial fluid was obtained at a mean of 3.4 years (SD 1.3) postoperatively. The in vivo polyethylene wear particles were isolated from the synovial fluid using a previously validated method and examined by scanning electron microscopy. Results: The total number of polyethylene wear particles obtained from the knees with E1 (mean 6.9, SD 4.0 × 10 7 counts/knee) was greater than that obtained from those with ArCom (mean 2.2, SD 2.6 × 10 7 counts/knee) (p = 0.001). The particle size (equivalent circle of diameter) from the knees with E1 was smaller (mean 0.5 μm, SD 0.1) than that of knees with ArCom (mean 1.5, SD 0.3 μm) (p = 0.001). The aspect ratio of particles from the knees with E1 (mean 1.3, SD 0.1) was smaller than that with ArCom (mean 1.4, SD 0.1) (p < 0.001 ). Conclusion: This is the first report of in vivo wear particle analysis of E1. E1 polyethylene did not reduce the number of in vivo polyethylene wear particles compared with ArCom in early clinical stage. Further careful follow-up of newly introduced E1 for TKA should be carried out. Cite this article: Bone Joint J 2020;102-B(11):1527–1534.